2020
DOI: 10.11604/pamj.2020.36.254.23720
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and general procrastination in nurses: a cross-sectional study

Abstract: Introduction nurses are responsible for taking care of the health of the general public. Nurses´ own health is among the important factors affecting the quality of patient care. Self-Rated Health (SRH) is one of the indicators used extensively in health research for the assessment of the health status of individuals. The present study was conducted to evaluate self-rated health and its relationship with general procrastination in nurses. Methods the present cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Studies have found that poor economic status and underlying disease were negatively associated with self-rated health. 27, 28 The inability to access health resources due to financial hardship aggravates psychological distress and causes deterioration of overall well-being, making it more challenging to afford medications. 29 This may explain our findings that respondents from high-income households were more likely to be adherent compared to lower-income families irrespective of their disease status or the risk factor groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that poor economic status and underlying disease were negatively associated with self-rated health. 27, 28 The inability to access health resources due to financial hardship aggravates psychological distress and causes deterioration of overall well-being, making it more challenging to afford medications. 29 This may explain our findings that respondents from high-income households were more likely to be adherent compared to lower-income families irrespective of their disease status or the risk factor groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, nursing professionals self-assessed health through the selection of symptoms present in the past week, which offered data to relate them to illness. Health self-assessment refers to the individual's perception of their general health status (14) . In this regard, Iranian (14) and Brazilian (13) research identified good health assessment in nursing professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Health self-assessment refers to the individual's perception of their general health status (14) . In this regard, Iranian (14) and Brazilian (13) research identified good health assessment in nursing professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procrastination is often described as a failure of self-regulation,2 and the behaviour is associated with stress, symptoms of depression and anxiety,3 4 poorer academic performance5 and negative effect on overall health and well-being 6. Previous research on procrastination has mainly focused on examining mechanisms behind the behaviour, for example, why people procrastinate and associations with personality traits such as impulsivity,7 and to a lesser extent on evaluating support that could be helpful in changing procrastination behaviours 8.…”
Section: Introductionmentioning
confidence: 99%